Pengaruh Pembelajaran Inovatif Berbasis Deep Dialog/Critical Thinking (DD/CT) Terhadap Kemampuan Berpikir Kritis Dan Hasil Belajar Siswa Pada Matapelajaran Ekonomi Di MA NW Suralaga - Qurratul Aini (Universitas Hamzanwadi, 2018)
This study aims to determine the effect of the innovative learning-based deep dialogue / critical thinking (DD / CT) against critical thinking skills and student learning outcomes in economic lesson in MA NW Suralaga. This type of research using a quasi-experimental methods (quasi experimental) research design Non-Equivalent Control Group Design. The sampling technique is cluster random sampling. The study population was all students of class X in the MA NW Suralaga. X Class B as an experimental class, while the class X C as the control class. The instrument used in this study is the observation sheet and tests. The results of calculations prerequisite test data analysis done by the normality test results homogeneity test using the test of Bartlet, while the hypothesis test result obtained t between models of deep dialogue / critical thinking (DD / CT) with the critical thinking skills of students at 4:18, while t table on significance level Î± = 0.05 (5%) is 2.098, whereas the t between models of deep dialogue / critical thinking (DD / CT) with the learning outcomes of 7.9 and t table of 2.098. Because t count t table means H0 rejected and Ha accepted. Thus, the results of this study indicate that the use of models of deep dialogue / critical thinking (DD / CT) effect on critical thinking skills and student learning outcomes MA NW Suralaga